Solid electrolyte, electrode, and solid electrolyte battery
Patent Information
- Application Number
- JP2023124530
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0015】 本実施形態に係る固体電解質を用いた固体電解質電池は、初期充放電効率が優れる。
Smart Images

Figure 2025020901000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid electrolyte, an electrode, and a solid electrolyte battery.
Background Art
[0002] In recent years, the development of electronics technology has been remarkable, and mobile electronic devices have been made smaller, lighter, thinner, and more multifunctional. There is a strong demand for batteries that power electronic devices to be smaller, lighter, thinner, and more reliable. For this reason, solid electrolyte batteries using solid electrolytes as electrolytes have attracted attention. As solid electrolytes, oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes (such as LiBH4), etc. are known.
[0003] Patent Document 1 discloses a predetermined halogen-based solid electrolyte. Patent Document 1 describes that by making the halogen-based solid electrolyte into a compound with a predetermined composition, the potential window of the solid electrolyte becomes larger and the ionic conductivity becomes higher.
[0004] Also, Patent Document 2 describes that a solid electrolyte represented by Li 1-a Al a X 1+2a (0 < a < 1, a ≠ 0.5, X is at least one selected from the group consisting of Cl, Br, and I) has high lithium ion conductivity.
[0005] Also, Non-Patent Document 1 describes a solid electrolyte represented by monoclinic LiAlCl4.
Prior Art Documents
Patent Documents
[0006]
Patent Document 1
Patent Document 2
Non-Patent Documents
[0007] [Non-Patent Document 1] Naoto Tanibata et al., ACS Materials Lett.2020, 2, 880―886. Summary of the Invention [Problem to be solved by the invention]
[0008] Solid electrolyte batteries using a solid electrolyte have a lower initial charge efficiency than lithium ion secondary batteries using a liquid electrolyte, and there is a demand for an improvement in the initial charge / discharge efficiency.
[0009] The present invention has been made in view of the above problems, and has an object to provide a solid electrolyte, an electrode, and a solid electrolyte battery that are excellent in initial charge / discharge efficiency. [Means for solving the problem]
[0010] [1] The solid electrolyte according to the first aspect is a E b G c X d In the formula (1), A is at least one element selected from the group consisting of Li, Na, Cs, and Ca, E is at least one element selected from the group consisting of Al, Ga, and In, and G is OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, SiO 11 , SiO 18 , PO3, PO4, P2O7, P3O 10, at least one group selected from the group consisting of SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, B((COO)2), (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO (maleate), OOC-CH=CH-COO (fumarate), C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO4, SeO4, TeO4, HCOO, SCN; X is at least one element selected from the group consisting of F, Cl, Br, I; a satisfies 0.5 ≦ a < 6; b satisfies 0 < b < 2; c satisfies 0.0001 ≦ c < 0.1; d satisfies 0 ≦ d ≦ 6.1.
[0011] [2] In the solid electrolyte according to the above aspect, G is a group represented by SO4 or PO4, and c and d may satisfy the relationship of 3 ≦ c + d ≦ 5.
[0012] [3] In the solid electrolyte according to the above aspect, G contains a sulfur element, X contains a chloride element, and the mass ratio of the sulfur element to the chloride element is 2.3×10 -5 ≦ S / Cl ≦ 2.3×10 -2 and may satisfy this.
[0013] [4] The electrode according to the second aspect includes the solid electrolyte according to the above aspect and an active material.
[0014] [5] The solid electrolyte battery according to the third aspect includes the solid electrolyte according to the above aspect.
Advantages of the Invention
[0015] The solid electrolyte battery using the solid electrolyte according to this embodiment has excellent initial charge-discharge efficiency.
Brief Description of the Drawings
[0016] [Figure 1] 1 is a schematic cross-sectional view of a solid electrolyte battery according to an embodiment of the present invention. [Diagram 2] 5 shows charge / discharge curves of Example 2, Comparative Example 1, and Comparative Example 5. [Diagram 3] 1 shows the results of XRD measurement for Example 3 and Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present embodiment will be described in detail below with reference to the drawings as appropriate. The drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may differ from the actual ones. The materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not limited thereto, and may be appropriately modified and implemented within the scope of the present invention.
[0018] "Solid electrolyte" A solid electrolyte is a material that can move ions when an external electric field is applied. Solid electrolytes can be used as part of the solid electrolyte layer and electrodes of solid electrolyte batteries.
[0019] The solid electrolyte according to this embodiment is A a E b G c X d The solid electrolyte contains a compound represented by the formula (1). In addition to the compound, the solid electrolyte may contain unavoidable impurities, materials derived from raw materials, and the like.
[0020] In formula (1), A is at least one element selected from the group consisting of Li, Na, Cs, and Ca, E is at least one element selected from the group consisting of Al, Ga, and In, and G is OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, SiO7, Si3O9, SiO 11 , SiO 18, PO3, PO4, P2O7, P3O 10 , SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, B((COO)2), (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO (maleate), OOC-CH=CH-COO (fumarate), C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO4, SeO4, TeO4, HCOO, SCN, and is at least one group selected from the group consisting of; X is at least one element selected from the group consisting of F, Cl, Br, and I; a satisfies 0.5 ≦ a < 6; b satisfies 0 < b < 2; c satisfies 0.0001 ≦ c < 0.1; and d satisfies 0 ≦ d ≦ 6.1.
[0021] The solid electrolyte may be in the form of powder (particles) or a sintered body obtained by sintering the powder. The solid electrolyte may also be a molded body obtained by compressing and molding the powder, a molded body obtained by molding a mixture of the powder and a binder, or a coating film formed by applying a paint containing the powder, the binder, and a solvent and then heating to remove the solvent. The main structure of the solid electrolyte may be amorphous or crystalline.
[0022] In formula (1), A is at least one element selected from the group consisting of Li, Na, Cs, and Ca. It is preferable that A contains only Li or a part of Li is substituted with Na, Cs, or Ca. When a part of Li is substituted with Na, Cs, or Ca, the potential window on the reduction side of the solid electrolyte becomes wider.
[0023] For example, when A contains Li and Cs, the ratio of Li to Cs is preferably 0.03 to 0.20 in molar ratio (Cs / Li), and more preferably 0.04 to 0.10 in molar ratio (Ca / Li). For example, when A contains Li and Ca, the ratio of Li to Ca is preferably 0.03 to 0.20 in molar ratio (Ca / Li), and more preferably 0.04 to 0.10 in molar ratio. When the solid electrolyte satisfies these relationships, the potential window on the reduction side of the solid electrolyte becomes wider.
[0024] In formula (1), a satisfies 0.5≦a<6, preferably 2.0≦a≦4.0, and more preferably 2.5≦a≦3.5. In the compound represented by formula (1), when a satisfies 0.5≦a<6, the Li content in the compound becomes appropriate, and the ionic conductivity of the solid electrolyte becomes high.
[0025] In formula (1), E is an essential component and is an element that forms the framework of the solid electrolyte. E is at least one element selected from the group consisting of Al, Ga, and In. By containing E, the solid electrolyte has a wider potential window and higher ionic conductivity. Al, Ga, and In are elements in the same group in the periodic table. Furthermore, a solid electrolyte in which E is at least one element selected from the group consisting of Al, Ga, and In has a wider potential window and is particularly excellent in reduction resistance. The reason why E is excellent in reduction resistance when E is Al, Ga, or In is unclear, but is thought to be as follows. Al 3+ Ga has a small ionic radius of 0.535 Å and a large positive charge of +3, making it highly polarizable. When E is an element with high polarity, the solid electrolyte tends to have excellent reduction resistance. 3+ and In 3+ The ionic radii of Ga are small, 0.62 Å and 0.8 Å, respectively, and the charge is +3, which is large and positively charged. 3+ and In 3+ Al 3+ Similarly, it has high polarity. Therefore, E element is Al 3+ , Ga 3+ and In 3+The solid electrolyte is considered to be excellent in reduction resistance.
[0026] In formula (1), b satisfies 0 < b < 2. Since the effect of including E can be obtained more effectively, b is preferably 0.6 ≤ b. Also, when b ≤ 1, the density of the solid electrolyte becomes low, and it becomes easier to secure a path for ion conduction.
[0027] In formula (1), G is at least one group selected from the group consisting of OH, BO2, BO3, BO4, B3O6, B4O7, CO3, NO3, AlO2, SiO3, SiO4, Si2O7, Si3O9, Si4O 11 、Si6O 18 、PO3, PO4, P2O7, P3O 10 、SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, S2O8, BF4, PF6, B((COO)2), (COO)2, N, AlCl4, CF3SO3, CH3COO, CF3COO, OOC-(CH2)2-COO, OOC-CH2-COO, OOC-CH(OH)-CH(OH)-COO, OOC-CH(OH)-CH2-COO, C6H5SO3, OOC-CH=CH-COO (maleate), OOC-CH=CH-COO (fumarate), C(OH)(CH2COOH)2COO, AsO4, BiO4, CrO4, MnO4, PtF6, PtCl6, PtBr6, PtI6, SbO4, SeO4, TeO4, HCOO, SCN.
[0028] B((COO)2) is bisoxalate borate, OOC-(CH2)2-COO is succinate, OOC-CH2-COO is malonate, OOC-CH(OH)-CH(OH)-COO is tartrate, OOC-CH(OH)-CH2-COO is malate, C6H5SO3 is benzenesulfonate, OOC-CH=CH-COO is maleate, OOC-CH=CH-COO is fumarate, C(OH)(CH2COOH)2COO is citrate. Maleic acid is the trans form, fumaric acid is the cis form, and they have the same chemical formula but are in a geometric isomer relationship.
[0029] G is preferably, for example, SO4 (sulfate) or PO4 (phosphate), and particularly preferably sulfate. Sulfate and phosphate have strong covalent bonds with E and are difficult to be reduced.
[0030] In the compound represented by formula (1), 0.0001 ≦ c < 0.1. That is, G is added in a trace amount in the solid electrolyte as compared with other elements. G substitutes for a part of the halogen (X) described later. This trace amount of G is considered to be electrolyzed during charging of the solid electrolyte battery and form a protective film on the surface of the active material and the solid electrolyte. This protective film suppresses the electrolysis of the active material and suppresses the decrease in charge-discharge efficiency. Also, when the addition amount of G is large, impurities caused by G may precipitate at the grain boundaries of the solid electrolyte crystals. The ionic radius of halogen (for example, Cl - is 1.81 Å), while the ionic radius of G (for example, SO4 2- is 2.3 Å, PO4 3- is 2.38 Å, CF3COO - is 2.66 Å) is large, and G that could not be substituted by halogen may precipitate. This precipitate may hinder the movement of ions and cause a decrease in ionic conductivity.
[0031] In formula (1), X is at least one selected from the group consisting of F, Cl, Br, and I. When the solid electrolyte contains X, the ionic conductivity of the solid electrolyte increases. It is particularly preferable that X contains Cl. When X is Cl, it becomes a solid electrolyte with high ionic conductivity and a good balance of oxidation resistance and reduction resistance.
[0032] In the compound represented by formula (1), 0 < d ≦ 6.1. In the compound represented by formula (1), it is preferable that d ≧ 1. When d ≧ 1, when the solid electrolyte is pressure-molded into a pellet shape, a pellet having sufficient strength can be obtained. Also, when d ≧ 1, the effect of increasing the ionic conductivity due to the inclusion of X can be sufficiently obtained.
[0033] The solid electrolyte according to this embodiment is, for example, LiAlCl4, LiGaCl4, or LiInCl4 in which a part of the chloride ions is substituted with a small amount of a group represented by G.
[0034] The sum of anions represented by the sum of c and d in formula (1) preferably satisfies 3≦c+d≦5, and particularly preferably c+d=4. When the abundance ratio of the anions does not deviate significantly from that of the compound before substitution with the group represented by G, the electrical stability of the solid electrolyte can be maintained.
[0035] The mass ratio of sulfur and chloride in the solid electrolyte is 2.3×10 -5 ≦S / Cl≦2.3×10 -2 It is preferable that the following is satisfied. The sulfur element is an element derived from G, and is contained in the solid electrolyte when G contains any one of SO3, SO4, SO5, S2O3, S2O4, S2O5, S2O6, S2O7, and S2O8. The chloride element is an element derived from X, and is contained in the solid electrolyte when X contains Cl. The mass ratio of the sulfur element to the chloride element can be determined from the results of analysis using an ICP (inductively coupled plasma atomic emission spectrometry) device (manufactured by Shimadzu Corporation).
[0036] (Method of manufacturing solid electrolyte) When the solid electrolyte is in a powder state, it can be produced, for example, by a mechanochemical method. For example, raw material powders containing predetermined elements in a predetermined molar ratio are mixed and reacted. When the solid electrolyte is in a sintered state, it can be produced, for example, by a solid-phase reaction method. For example, raw material powders containing predetermined elements in a predetermined molar ratio are mixed and molded, and sintered in a vacuum or in an inert gas atmosphere.
[0037] When the raw material powder contains a halide raw material, the halide raw material is likely to evaporate when the temperature is increased. For this reason, a halogen gas may be made to coexist in the atmosphere during sintering to compensate for the halogen. For this reason, a halogen gas may be made to coexist in the atmosphere during sintering to compensate for the halogen. In addition, when the raw material powder contains a halide raw material, sintering may be performed by a hot press method using a mold with high sealing properties. In this case, since the mold has high sealing properties, evaporation of the halide raw material due to sintering can be suppressed. By sintering in this manner, a solid electrolyte in the form of a sintered body made of a compound having a predetermined composition is obtained.
[0038] In this embodiment, in the manufacturing process of the solid electrolyte, heat treatment may be performed as necessary. By performing heat treatment, the crystallite size of the solid electrolyte can be adjusted. For example, in an argon gas atmosphere, heat treatment is preferably performed at a temperature of 130°C to 650°C for 0.5 hours to 60 hours, and more preferably at a temperature of 175°C to 600°C for 1 hour to 30 hours. By performing heat treatment in an argon gas atmosphere at a temperature of 150°C to 550°C for 5 hours to 24 hours, the crystallite size of the solid electrolyte can be set to 5 nm to 500 nm.
[0039] The solid electrolyte of the present embodiment is made of the compound represented by formula (1), and therefore has excellent initial charge-discharge efficiency. Although the details of the reason are unclear, it is believed that this is because G, which replaces a small amount of halogen, is electrolyzed during charging to form a coating that protects the active material.
[0040] [Solid electrolyte battery] Fig. 1 is a cross-sectional schematic diagram of a solid electrolyte battery according to this embodiment. The solid electrolyte battery 10 shown in Fig. 1 includes a positive electrode 1, a negative electrode 2, and a solid electrolyte layer 3. The solid electrolyte layer 3 is sandwiched between the positive electrode 1 and the negative electrode 2. The above-mentioned solid electrolyte may be included in the solid electrolyte layer 3, or may be included in the positive electrode 1 or the negative electrode 2, or may be included in both of them. The positive electrode 1 and the negative electrode 2 are connected to external terminals (not shown) and are electrically connected to the outside.
[0041] The solid electrolyte battery 10 charges or discharges by transferring ions between the positive electrode 1 and the negative electrode 2 via the solid electrolyte layer 3, and transferring electrons via an external circuit. The solid electrolyte battery 10 may be a laminate in which the positive electrode 1, the negative electrode 2, and the solid electrolyte layer 3 are laminated, or may be a wound body in which the laminate is wound. The solid electrolyte battery is used, for example, in laminate batteries, square batteries, cylindrical batteries, coin batteries, button batteries, etc.
[0042] <Solid electrolyte layer> The solid electrolyte layer 3 is sandwiched between the positive electrode 1 and the negative electrode 2. The solid electrolyte layer 3 includes a solid electrolyte that can move ions by an externally applied voltage. For example, the solid electrolyte conducts lithium ions and inhibits the movement of electrons.
[0043] The solid electrolyte layer 3 is, for example, a halide-based solid electrolyte. The solid electrolyte layer 3 includes, for example, the above-mentioned solid electrolyte. When the above-mentioned solid electrolyte is included in the positive electrode 1 or the negative electrode 2, the solid electrolyte included in the solid electrolyte layer 3 does not have to be the above-mentioned one.
[0044] <Positive electrode> 1, the positive electrode 1 has a plate-like (foil-like) positive electrode current collector 1A and a positive electrode mixture layer 1B. The positive electrode mixture layer 1B is in contact with at least one surface of the positive electrode current collector 1A.
[0045] "Positive electrode current collector" The positive electrode current collector 1A may be made of any electronically conductive material that is resistant to oxidation during charging and is not easily corroded. The positive electrode current collector 1A may be made of, for example, a metal such as aluminum, stainless steel, nickel, or titanium, or a conductive resin. The positive electrode current collector 1A may be in the form of a powder, a foil, a punched piece, or an expanded piece.
[0046] "Positive electrode mixture layer" The positive electrode mixture layer 1B contains a positive electrode active material, and optionally contains a solid electrolyte, a binder, and a conductive assistant.
[0047] (Cathode active material) The positive electrode active material is not particularly limited as long as it can reversibly absorb and release, and insert and remove (intercalate and deintercalate) lithium ions. As the positive electrode active material, a positive electrode active material used in a known lithium ion secondary battery can be used. As the positive electrode active material, for example, lithium-containing metal oxide, lithium-containing metal phosphate, etc. can be mentioned.
[0048] Lithium-containing metal oxides include, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and lithium manganese oxides represented by the general formula: LiNi x Co y Mn z O2 (x+y+z=1), lithium vanadium compounds (LiVOPO4, Li3V2(PO4)3), olivine-type LiMPO4 (where M represents at least one selected from Co, Ni, Mn, and Fe), lithium titanate (Li4Ti5O 12 ) etc.
[0049] The positive electrode active material may not contain lithium. Examples of such positive electrode active materials include non-lithium-containing metal oxides (MnO2, V2O5, etc.), non-lithium-containing metal sulfides (MoS2, etc.), and non-lithium-containing fluorides (FeF3, VF3, etc.). When using a positive electrode active material that does not contain lithium, the negative electrode is doped with lithium ions in advance, or a negative electrode containing lithium ions is used.
[0050] (binder) The positive electrode mixture layer 1B may contain a binder. The binder bonds the positive electrode active material, the solid electrolyte, and the conductive assistant that constitute the positive electrode mixture layer 1B to each other. The binder also bonds the positive electrode mixture layer 1B to the positive electrode current collector 1A. The binder preferably has oxidation resistance and good adhesiveness.
[0051] Examples of the binder used in the positive electrode mixture layer 1B include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid (PA) and its copolymer, metal ion crosslinked polyacrylic acid (PA) and its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or a mixture thereof. Among these, it is particularly preferable to use PVDF as the binder.
[0052] The content of the binder in the positive electrode mixture layer 1B is not particularly limited, but is preferably 1% by mass to 15% by mass, more preferably 3% by mass to 5% by mass, based on the total mass of the positive electrode active material, solid electrolyte, conductive assistant, and binder. If the amount of binder is too small, it tends not to be possible to form a positive electrode 1 with sufficient adhesive strength. Conversely, if the amount of binder is too large, it tends to be difficult to obtain sufficient volume or mass energy density, since general binders are electrochemically inactive and do not contribute to discharge capacity.
[0053] (solid electrolyte) The positive electrode mixture layer 1B may contain a solid electrolyte. The solid electrolyte is, for example, the above-mentioned solid electrolyte. The content of the solid electrolyte in the positive electrode mixture layer 1B is not particularly limited, but is preferably 1% by volume or more and 50% by volume or less, and more preferably 5% by volume or more and 30% by volume or less, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder.
[0054] (Conductive assistant) The conductive assistant improves the electronic conductivity of the positive electrode mixture layer 1B. Known conductive assistants can be used. The conductive assistant is, for example, a carbon material such as carbon black, graphite, carbon nanotubes, graphene, etc., a metal such as aluminum, copper, nickel, stainless steel, iron, or amorphous metal, a conductive oxide such as ITO, or a mixture thereof. The conductive assistant may be in the form of a powder or fiber.
[0055] The content of the conductive assistant in the positive electrode mixture layer 1B is not particularly limited. When the positive electrode mixture layer 1B contains the conductive assistant, the content is preferably 0.5% by mass or more and 20% by mass or less, and more preferably 1% by mass or more and 5% by mass or less, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder.
[0056] <Negative electrode> 1, the negative electrode 2 has a negative electrode current collector 2A and a negative electrode mixture layer 2B. The negative electrode mixture layer 2B is in contact with at least one surface of the negative electrode current collector 2A.
[0057] "Negative electrode current collector" The negative electrode current collector 2A may have electrical conductivity. For example, a metal such as copper, aluminum, nickel, stainless steel, or iron, or a conductive resin foil may be used as the negative electrode current collector 2A. The negative electrode current collector 2A may be in the form of a powder, a foil, a punching, or an expandable material.
[0058] "Negative electrode mixture layer" The negative electrode mixture layer 2B contains a negative electrode active material, and optionally contains a solid electrolyte, a binder, and a conductive assistant.
[0059] (Negative electrode active material) The negative electrode active material is not particularly limited as long as it can reversibly absorb and release lithium ions and insert and extract lithium ions. As the negative electrode active material, any negative electrode active material used in known solid electrolyte batteries can be used.
[0060] Examples of the negative electrode active material include carbon materials such as natural graphite, artificial graphite, mesocarbon microbeads, mesocarbon fibers (MCF), cokes, glassy carbon, and organic compound sintered bodies, Si, SiO x Metals that can combine with lithium, such as Sn and aluminum, their alloys, composites of these metals and carbon materials, lithium titanate (Li4Ti5O 12 ), oxides such as SnO2, metallic lithium, etc. The negative electrode active material is preferably natural graphite.
[0061] (binder) The negative electrode mixture layer 2B may contain a binder. The binder bonds the negative electrode active material, the solid electrolyte, and the conductive additive that constitute the negative electrode mixture layer 2B together. The binder also bonds the negative electrode mixture layer 2B and the negative electrode current collector 2A together.
[0062] Examples of the binder used in the negative electrode mixture layer 2B include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PA) and its copolymer, metal ion crosslinked polyacrylic acid (PA) and its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or a mixture thereof. Among these, it is preferable to use one or more types selected from SBR, CMC, and PVDF as the binder.
[0063] The binder content in the negative electrode mixture layer 2B is not particularly limited, but is preferably from 1 mass % to 15 mass %, and more preferably from 1.5 mass % to 10 mass %, based on the total mass of the negative electrode active material, the conductive assistant, and the binder.
[0064] (solid electrolyte) The negative electrode mixture layer 2B may contain a solid electrolyte. The solid electrolyte is, for example, the above-mentioned solid electrolyte. The content of the solid electrolyte is not particularly limited, but is preferably 1% by volume or more and 50% by volume or less, and more preferably 5% by volume or more and 30% by volume or less, based on the total mass of the negative electrode active material, the solid electrolyte, the conductive assistant, and the binder.
[0065] (Conductive assistant) The conductive assistant contained in the negative electrode mixture layer 2B may be the same as that in the positive electrode mixture layer 1B. The content of the conductive assistant in the negative electrode mixture layer 2B is preferably 0.5% by mass or more and 20% by mass or less, and more preferably 1% by mass or more and 12% by mass or less, relative to the negative electrode active material.
[0066] <Exterior body> The exterior body houses a battery element consisting of a positive electrode 1, a solid electrolyte layer 3, and a negative electrode 2. The exterior body prevents moisture and the like from entering from the outside to the inside. The exterior body is, for example, a metal laminate film made by coating both sides of a metal foil with a polymer film. The metal laminate film is formed into a bag shape and the opening is heat sealed to make the exterior body.
[0067] The metal foil is, for example, an aluminum foil, a stainless steel foil, etc. The polymer film arranged on the outside of the exterior body is preferably made of a polymer with a high melting point, such as polyethylene terephthalate (PET), polyamide, etc. The polymer film arranged on the inside of the exterior body is, for example, polyethylene (PE), polypropylene (PP), etc.
[0068] <External terminal> The external terminals include a positive electrode terminal and a negative electrode terminal. The positive electrode terminal is electrically connected to the positive electrode 1, and the negative electrode terminal is electrically connected to the negative electrode 2. The external terminals are made of a conductive material such as aluminum or nickel.
[0069] [Method of manufacturing solid electrolyte battery] Next, a method for producing a solid electrolyte battery according to the present embodiment will be described. First, the solid electrolyte according to the present embodiment is produced by the above-mentioned method.
[0070] Next, the positive electrode 1 is prepared. The positive electrode 1 is produced by applying a paste containing a positive electrode active material onto a positive electrode current collector 1A and drying it to form a positive electrode mixture layer 1B. The above-mentioned solid electrolyte may be added to the paste containing the positive electrode active material.
[0071] Next, the negative electrode 2 is prepared. The negative electrode 2 is produced by applying a paste containing a negative electrode active material onto a negative electrode current collector 2A and drying it to form a negative electrode mixture layer 2B. The above-mentioned solid electrolyte may be added to the paste containing the negative electrode active material.
[0072] The battery element can be produced, for example, by powder molding. A guide with a hole is placed on the positive electrode 1, and the guide is filled with a solid electrolyte. The surface of the solid electrolyte is then smoothed, and the negative electrode 2 is placed on top of the solid electrolyte. This sandwiches the solid electrolyte between the positive electrode 1 and the negative electrode 2. Pressure is then applied to the positive electrode 1 and the negative electrode 2 to pressure-mold the solid electrolyte. By pressure molding, a laminate is obtained in which the positive electrode 1, solid electrolyte layer 3, and negative electrode 2 are stacked in this order.
[0073] Next, external terminals are welded to the positive electrode current collector 1A of the positive electrode 1 and the negative electrode current collector 2A of the negative electrode 2, which form the laminate, by a known method, to electrically connect the positive electrode current collector 1A or the negative electrode current collector 2A to the external terminal. Thereafter, the laminate connected to the external terminal is housed in an exterior body, and the opening of the exterior body is heat-sealed to seal it. Through the above steps, the solid electrolyte battery of this embodiment is obtained.
[0074] The solid electrolyte battery according to this embodiment contains a solid electrolyte of a predetermined composition, and therefore has excellent initial charge-discharge efficiency. This is believed to be because the solid electrolyte contains a small amount of a group represented by G. The small amount of the group represented by G added is electrolyzed during charging, forming a coating that protects the active material. It is believed that this coating suppresses the electrolysis of the active material, thereby increasing the initial charge-discharge efficiency of the solid electrolyte battery.
[0075] The above describes the embodiments of the present invention in detail with reference to the drawings. However, each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. EXAMPLES
[0076] "Example 1" (Preparation of solid electrolyte) In a glove box with a dew point of approximately -65 to -80°C, raw material powders of lithium chloride (LiCl), lithium sulfate (Li2SO4), and aluminum chloride (AlCl3) were weighed out to have a molar ratio of 0.9999:0.0001:1.000, respectively. The raw material powders were mixed and reacted for 24 hours using a planetary ball mill with a rotation speed of 500 rpm and a revolution speed of 500 rpm, with the rotation direction and the revolution direction reversed. Then, Li 1.0001 Al(SO4) 0.0001 Cl 3.999 The composition of the solid electrolyte was determined using an ICP (inductively coupled plasma atomic emission spectrometry) device (manufactured by Shimadzu Corporation).
[0077] The planetary ball mill is installed in a normal atmosphere (air). The zirconia sealed container for the planetary ball mill is screwed and sealed with polyimide tape, and when the zirconia sealed container is set in the planetary ball mill, the zirconia sealed container is firmly pressed and fixed in place. Therefore, even in a normal atmosphere, it is believed that there is almost no moisture from the air entering the zirconia sealed container.
[0078] [Measurement of ionic conductivity] Next, in a glove box with argon gas circulating at a dew point of approximately -70°C, the obtained solid electrolyte powder was filled into a pressure molding die and pressure molded under a load of approximately 30 KN to prepare a measurement cell for ionic conductivity.
[0079] The pressure molding die is composed of a PEEK (polyether ether ketone) cylinder with a diameter of 10 mm, and upper and lower punches made of SKD11 material with a diameter of 9.99 mm.
[0080] After that, a stainless steel disk and a Teflon (registered trademark) disk, both 50 mm in diameter and 5 mm thick with four screw holes, were prepared and the pressure molding die was set as follows. They were loaded in the following order: stainless steel disk / Teflon (registered trademark) disk / pressure molding die / Teflon (registered trademark) disk / stainless steel disk, and the four screws were tightened with a torque of approximately 3 N m. Screws were also inserted into the screw holes on the sides of the upper and lower punches to serve as external connection terminals.
[0081] The external connection terminal was connected to a potentiostat (VersaSTAT3 manufactured by Princeton Applied Research) equipped with a frequency response analyzer, and the ionic conductivity was measured using an impedance measurement method. The measurement was performed in the measurement frequency range of 1 MHz to 0.1 Hz, with an amplitude of 10 mV and at a temperature of 25°C. The ionic conductivity of the solid electrolyte of Example 1 was 9.4 × 10 -6 It was S / cm.
[0082] [Measurement of initial charge / discharge efficiency] First, a solid electrolyte battery was fabricated to measure the initial charge / discharge efficiency.
[0083] The positive electrode active material, solid electrolyte, and conductive additive were weighed out to a ratio of 81 parts by mass, 16 parts by mass, and 3 parts by mass, and mixed in an agate mortar to prepare a positive electrode mixture. The positive electrode active material was lithium cobalt oxide (LiCoO2), the solid electrolyte was prepared by the procedure described above, and the conductive additive was carbon black.
[0084] Next, the negative electrode active material, the solid electrolyte, and the conductive additive were weighed out to be 67 parts by mass, 30 parts by mass, and 3 parts by mass, and mixed in an agate mortar to prepare a negative electrode mixture. The negative electrode active material was graphite, the solid electrolyte was the one prepared by the above procedure, and the conductive additive was carbon black. This was used as a negative electrode mixture.
[0085] The lower punch was inserted into the resin holder, and 110 mg of solid electrolyte was added from the top of the resin holder. The upper punch was inserted onto the solid electrolyte. This set was placed in a press and pressure-molded at a pressure of 373 MPa. The set was then removed from the press, and the upper punch was removed.
[0086] Next, 39 mg of the previously prepared positive electrode mixture was placed on top of the solid electrolyte (pellet-shaped) in the resin holder. Then, an upper punch was inserted from above, and pressure molding was performed with a press machine under a pressure of 373 MPa. Next, this set was taken out, turned upside down, and the lower punch was removed. Next, 20 mg of the negative electrode mixture was placed on top of the solid electrolyte (pellet). Then, a lower punch was inserted on top of it, and pressure molding was performed with a press machine under a pressure of 373 MPa.
[0087] By the above procedure, a battery element was produced in which the positive electrode, the solid electrolyte, and the negative electrode were laminated in this order in the resin holder. Screws were inserted as terminals for charging and discharging into the screw holes on the sides of the upper and lower punches.
[0088] Then, an aluminum laminate material was prepared as the material for the exterior body that encapsulates the battery elements. The aluminum laminate material is made of PET(12) / Al(40) / PP(50). PET is polyethylene terephthalate, and PP is polypropylene. The numbers in parentheses indicate the thickness of each layer (unit: μm). This aluminum laminate material was cut to A4 size and folded back in the middle of the long side so that the PP was on the inner surface.
[0089] An aluminum foil (width 4 mm, length 40 mm, thickness 100 μm) was prepared as the positive electrode terminal. A nickel foil (width 4 mm, length 40 mm, thickness 100 μm) was prepared as the negative electrode terminal. Acid-modified polypropylene was wrapped around each of these external terminals (positive electrode terminal and negative electrode terminal) and thermally bonded to the exterior body. This was to improve the sealing between the external terminals and the exterior body.
[0090] A positive electrode terminal and a negative electrode terminal were placed in the middle of each of the two opposing sides of the folded aluminum laminate material, and heat-sealed. Then, a battery element was inserted into the exterior body, and the positive electrode terminal was electrically connected to the positive electrode terminal inside the exterior body by connecting the screw on the side of the upper punch to the lead wire. Also, the negative electrode terminal was electrically connected to the negative electrode terminal by connecting the screw on the side of the lower punch to the lead wire. Then, the opening of the exterior body was heat-sealed to form a solid electrolyte battery.
[0091] Charging and discharging tests of solid electrolyte batteries were carried out in a thermostatic chamber at 25°C. The C (C) rate was used to indicate the charging and discharging current. nC (mA) is the current at which the nominal capacity (mAh) can be charged and discharged at 1 / n (h). For example, for a battery with a nominal capacity of 70mAh, the current at 0.05C is 3.5mA (calculation formula: 70 x 0.05 = 3.5). Similarly, the current at 0.2C is 14mA, and the current at 2C is 140mA. Charging was performed at 0.2C up to 4.2V at constant current constant voltage (CCCV). Charging was completed when the current was 1 / 20C. Discharging was performed at 0.2C down to 3.0V.
[0092] The initial charge capacity and initial discharge capacity were then measured, and the initial charge / discharge efficiency ("initial discharge capacity" / "initial charge capacity" x 100) was measured. The solid electrolyte of Example 1 had an initial charge capacity of 168 mAhg -1 The initial discharge capacity is 154mAhg. -1 The initial charge / discharge efficiency was 91.7%.
[0093] "Examples 2 to 78 and Comparative Examples 1 to 6" Examples 2 to 78 and Comparative Examples 1 to 6 were all performed in the same manner as Example 1, except that the raw materials and their molar ratios when preparing the solid electrolyte were changed. The raw materials for the solid electrolyte, their molar ratios, and the composition of the prepared solid electrolyte are shown in Table 1. Examples 1 to 6 are A a E b G c X d G was fixed to SO4 and the value of c was changed. Examples 7 to 12 are the same as Examples 1 to A. a E b G c X d The G was changed to PO3 and the value of c was changed. Examples 13 to 15 are the same as Examples 1 to A. a E b G c X d The E was changed to Ga and the value of c was changed. Examples 16 to 18 are the same as Examples 1 to A. a E b G c X d The E in was changed to In and the value of c was changed. Examples 19 to 78 are the same as Examples 4 to A. a E b G c X d In addition, in Examples 34 to 44, the A in Example 4 was changed. a E b G c X d The values of c and d were also changed along with G. Example 59 is a case where G is maleic acid, and Example 60 is a case where G is fumaric acid. Example 75 is a mixture of Example 3 to A. a E b G c X d The X in was changed. Examples 76 to 78 are the same as Examples 2 to A. a E b G c X d The A in has been changed. Comparative Examples 1 to 4 are a E b G c X dThe value of c is large. Comparative Example 5 is A a E b G c X d It does not have the G. Comparative Example 6 is A a E b G c X d The E is Zr.
[0094] The results of Examples 1 to 78 and Comparative Examples 1 to 6 are summarized in the following table.
[0095] [Table 1]
[0096] [Table 2]
[0097] [Table 3]
[0098] [Table 4]
[0099] [Table 5]
[0100] [Table 6]
[0101] The solid electrolyte batteries using the solid electrolytes shown in Examples 1-78 all had superior initial charge / discharge efficiency to the solid electrolyte batteries using the solid electrolytes shown in Comparative Examples 1-6.
[0102] The charge / discharge curves of Example 2, Comparative Example 1, and Comparative Example 5 are shown in FIG.
[0103] 3 shows the results of X-ray diffraction (XRD) for Example 3 and Comparative Example 5. The method for measuring XRD for Example 3 and Comparative Example 5 is described below.
[0104] XRD measurement of the solid electrolyte of Example 3 was carried out at the large synchrotron radiation facility Spring-8. In a glove box with a dew point of about -90°C in which argon gas was circulating, the solid electrolyte powder of Example 3 was filled into a glass capillary, and the open end of the glass capillary was melted and sealed. XRD measurement was carried out on this at Spring-8. The diffraction angle 2θ was converted to a value assuming that the measurement wavelength of XRD was 0.799407 Å.
[0105] In addition, in a glove box with a dew point of about -90°C in which argon gas is circulating, the obtained solid electrolyte powder of Comparative Example 5 was filled into an XRD measurement holder. Then, polyimide tape (dried in vacuum at 70°C for 16 hours) was attached and sealed to cover the filled surface for moisture prevention, and an XRD measurement sample was prepared. Then, it was taken out into the atmosphere and XRD measurement was performed using an X-ray diffractometer (X'PertPro manufactured by PANalytical Co., Ltd.). The X-ray source used was Cu-Kα radiation (measurement wavelength: 0.799407 Å). Under the same conditions as the above XRD measurement, only the Kapton polyimide tape used for moisture prevention was attached to the XRD measurement holder, and background measurement was performed.
[0106] As can be seen from FIG. 3, the three peaks of the solid electrolyte of Example 3 are shifted to the higher angle side compared to the peaks of Comparative Example 5. This is because part of the Cl in LiAlCl4 is converted to SO4 2- This means that it is replaced by [Explanation of symbols]
[0107] 1... positive electrode, 1A... positive electrode current collector, 1B... positive electrode mixture layer, 2... negative electrode, 2A... negative electrode current collector, 2B... negative electrode mixture layer, 3... solid electrolyte layer, 10... solid electrolyte battery
Claims
1. A a E b G c X d ... (1) In formula (1), A is at least one element selected from the group consisting of Li, Na, Cs, and Ca; E is at least one element selected from the group consisting of Al, Ga, and In; Gは、OH、BO 2 、BO 3 、BO 4 、B 3 O 6 、B 4 O 7 、CO 3 、NO 3 、AlO 2 、SiO 3 、SiO 4 、Si 2 O 7 、Si 3 O 9 、Si 4 O 11 、Si 6 O 18 、PO 3 、PO 4 、P 2 O 7 、P 3 O 10 、SO 3 、SO 4 、SO 5 、S 2 O 3 、S 2 O 4 、S 2 O 5 、S 2 O 6 、S 2 O 7 、S 2 O 8 、BF 4 、PF 6 、B((COO) 2 )、(COO) 2 、N、AlCl 4 、CF 3 SO 3 、CH 3 COO、CF 3 COO、OOC-(CH 2 ) 2 -COO、OOC-CH 2 -COO、OOC-CH(OH)-CH(OH)-COO、OOC-CH(OH)-CH 2 -COO、C 6 H 5 SO 3 , OOC-CH=CH-COO (maleate), OOC-CH=CH-COO (fumarate), C(OH)(CH 2 COOH) 2 COO, A.S.O. 4 , BiO 4 , CrO 4 , MnO 4 , PtF 6 , PtCl 6 , PtBr 6 , PtI 6 , SbO 4 , SeO 4 , TeO 4 , HCOO, SCN, X is at least one element selected from the group consisting of F, Cl, Br, and I; a satisfies 0.5≦a<6, b satisfies 0<b<2, c satisfies 0.0001≦c<0.1, A solid electrolyte in which d satisfies 0≦d≦6.
1.
2. The G is SO 4 or P.O. 4 is a group represented by The solid electrolyte according to claim 1 , wherein the c and the d satisfy the relationship 3≦c+d≦5.
3. The G contains a sulfur element, The X contains a chloride element, The mass ratio of sulfur element to chloride element is 2.3 × 10 -5 ≦S / Cl≦2.3×10 -2 The solid electrolyte according to claim 1 .
4. An electrode comprising the solid electrolyte according to claim 1 and an active material.
5. A solid electrolyte battery comprising the solid electrolyte according to claim 1.
Citation Information
Patent Citations
Solid electrolyte and solid electrolyte battery
WO2021261558A1
Solid electrolyte material and battery
WO2022137758A1
Cited By
Oxide solid electrolyte, preparation method thereof and solid-state battery
CN119890436A